2016
DOI: 10.1111/mafi.12140
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Equivalence of Risk Measures Under Dependence Uncertainty

Abstract: In this paper, we study the aggregate risk of inhomogeneous risks with dependence uncertainty, evaluated by a generic risk measure. We say that a pair of risk measures is asymptotically equivalent if the ratio of the worst‐case values of the two risk measures is almost one for the sum of a large number of risks with unknown dependence structure. The study of asymptotic equivalence is particularly important for a pair of a noncoherent risk measure and a coherent risk measure, as the worst‐case value of a noncoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Remark 4.4. The asymptotics as n → ∞ of the worst-case aggregate values of dual utilities (under the term distortion risk measures) has been studied in Wang et al (2015) and Cai et al (2018) under different settings. In particular, Cai et al (2018) showed that the ratio…”
Section: General Resultsmentioning
confidence: 99%
“…Remark 4.4. The asymptotics as n → ∞ of the worst-case aggregate values of dual utilities (under the term distortion risk measures) has been studied in Wang et al (2015) and Cai et al (2018) under different settings. In particular, Cai et al (2018) showed that the ratio…”
Section: General Resultsmentioning
confidence: 99%
“…For aggregate risk models, that is, n > 1 in (1), finding bounds for quantities related to the sum of random variables with the knowledge of marginal distributions is typically called the Fréchet problem, where the complete uncertainty of the dependence is typically assumed. For recent research on Fréchet problems for VaR and convex risk measures, see , Wang et al (2013), Bernard et al (2014) and Cai et al (2017). For VaR bounds with partial dependence information in addition to the marginal information, see Bernard et al (2016bBernard et al ( , 2017a, Bernard and Vanduffel (2015) and Puccetti et al (2016Puccetti et al ( , 2017, amongst others.…”
Section: Problem Formulation and Related Literaturementioning
confidence: 99%
“…The equivalence (2.2) was shown in Puccetti and Rüschendorf (2014) and Puccetti et al (2013) under different conditions, and with generality in . For equivalence of type (2.2) under the setting of inhomogeneous marginal distributions and for risk measures other than VaR and ES, see Embrechts et al (2015), and Cai et al (2017). The convergence rate of (2.2) is given in the following lemma:…”
Section: Lemma 26 (Corollary 37 Of Wang and Wang (2015)) For Any Dmentioning
confidence: 99%